"Letting go of the raft" – The art of spiritual leadership in contemporary organizations from a Buddhist perspective using skilful means. (June 2019) - Chi Vu, Mai; Gill, Roger
Organizations are diverse workplaces where various beliefs, values and perceptions are shared to varying extents. How can spiritual leadership induce altruistic love and intrinsic motivation among diverse members within the organization and without being regarded as really yet another covert, sophisticated form of corporate exploitation of human vulnerability reflective of the "dark side" of organizations and leadership? This paper explores an approach to spiritual leadership from a Buddhist perspective focusing on the power of skilful means to tackle such concerns. In organizational pursuits such as appearance, reputation, fame, power, recognition and even leader–follower relationships are associated mostly with objectives and expectations, known in Buddhism as "attachment". In Buddhism, however, any kind of attachment may be a source of suffering that eventually leads to negative consequences. In reviewing the dark side of spiritual leadership practices and how Buddhism is commoditized for organizational purposes, we reaffirm on the importance of the notion of non-attachment in Buddhism. We unpack the application of the Buddhist metaphor of "the raft", non-attachment and other Buddhist stories of skilful means in spiritual leadership and their contribution to leadership studies.